Indonesian stock market’s dynamic integration with Asian stock markets and world stock markets - Robiyanto, Robiyanto (Penerbit Universiti Kebangsaan Malaysia, 2018)
The study examines the relationship and integration of stock markets by using a DCC-GARCH from the period of January 1999 to September 2015. The period of January 1999 to September 2015 is chosen because in this period there has been a revocation of foreign ownership restrictions on the Indonesia Stock Exchange. By using this dynamic approach, the relationship, even the integration, of the ever-changing stock markets need to be analyzed with an approach that can accommodate and capture the dynamism of emerging stock markets studied in more detail. Beside DCC-GARCH, several additional analysis were also conducted. The data used in this study are the stock price index data on the stock markets studied namely Nikkei 225 index, Dow Jones Industrial Average (DJIA), FTSE index, All Ordinaries index, Straits Times Index (STI), SET index, KOSPI index, Taipei WG index, KLSE Composite Index, Hang Seng Index (HSI), Manila Composite index (PSEi) and Jakarta Composite Index (JCI). This study found that after subprime mortgage crisis in 2008, the Indonesian stock market was more integrated with several stock markets in Asia and especially in the stock markets in the ASEAN region. By separating the study period into three periods of pre-crisis, during crisis and post-crisis, this study found that the level of stock market integration in Indonesia with stock markets in Asia and the world is increasing. This study shows the importance of dynamic approach’s usage in stock market integration analysis.